Proposed conceptual model of construction firms' performance sustainability indicators in Malaysia - Ilias Said; Omar Osman; Waleed Rashideh; Mohd. Wira Mohd. Shafiei (Penerbit Universiti Sains Malaysia, 2015)
This book discussed all relevant materials regarding the achievement of sustainability in the construction industry.